Students’ Perceptions of the Use of ChatGPT in Improving English Writing Skills - Vanes Kuera; Maya Pinkan Warouw; F. Ari Anggraini Sebayang (JALL (Journal of Applied Linguistics and Literacy), 2026)
The integration of artificial intelligence (AI) in education has provided new opportunities to support English as a Foreign Language (EFL) writing development. One AI-based tool that has gained significant attention is ChatGPT, which offers immediate feedback, idea generation, and language support throughout the writing process. This study aims to explore students’ perceptions regarding the use of ChatGPT to improve English writing skills, with particular attention to its benefits, challenges, and the strategies employed by students when using the tool. This study employed a qualitative descriptive research design. Data were collected through semi-structured face-to-face interviews with six undergraduate students from the English Department of Sam Ratulangi University, Manado, who had experience using ChatGPT in academic writing contexts. The interview data were analyzed thematically following Creswell’s qualitative data analysis procedures. The findings indicate that students generally perceive ChatGPT as a useful writing support tool, especially for improving grammar and tense accuracy, assisting academic sentence construction, supporting idea generation, and functioning as an independent learning resource. However, students also reported several challenges, including limitations in output quality, increased writing complexity due to repeated revisions, and the risk of psychological dependence that may affect independent writing ability. To address these challenges, students applied strategies such as paraphrasing AI-generated text, refining prompts, selecting essential ideas, and maintaining control over drafting and revision processes. In conclusion, ChatGPT can effectively support EFL writing development when used critically and strategically. Therefore, guided and balanced integration of AI tools is recommended to enhance learning while preserving students’ writing autonomy.